2,5-Dioxopyrrolidin-1-yl 3-(furan-2-yl)acrylate - Zhu, Haifeng (International Union of Crystallography, 2011)
The title compound, C(11)H(9)NO(5), was prepared by the reaction of 2-furanacrylic acid and N-hydroxysuccinimide. The molecule consists of two approximately planar moieties, viz. a succinimide group and the rest of the molecule [the largest deviations from the least-squares planes are 0.120 (1) and 0.210 (1) Å, respectively]. The dihedral angle between these fragments is 63.70 (5)°. In the crystal, molecules are linked by C—H⋯O hydrogen bonds into two-dimensional nets.